Redeeming anthropology: a theological critique of a modern science - Furani, Khaled (Oxford University Press USA- OSO, 2019)
This book assembles a paradigm of anthropodom--anthropology governed and constituted by sovereign secular reason as a progeny of the Enlightenment--in order to explore existent and potential relations with its ostensible other, theology.